The Role And Responsibility Of Notaries In Improving The Validity Of Deeds And Legalization - Fistyarahma Nurshinta; Gunardi Gunardi (Publikasi Indonesia, 2023)
The notary has permission to legalize private deeds requested by the party. However, private deeds often contain elements of unlawful acts. This research aims to describe the responsibilities of notaries towards their profession as public officials who make authentic deeds, and to describe the responsibilities of notaries regarding private agreements that contain elements of unlawful acts that have been legalized. The method used in this article is normative juridical, namely the study of secondary data using a statutory approach and a conceptual approach that has analytical descriptive research specifications. The results of the research in this article are: firstly, the responsibility of a notary towards his profession as an official who makes authentic deeds is only limited to the formal form of authentic deeds, not to the contents of the deed, every action carried out by a notary can be held accountable if there is a violation committed and this action can cause losses. for the parties. Second, the notary's responsibility for private agreements that contain elements of unlawful acts that have been legalized, namely that the notary does not dispute the contents of the private deed even though it contains an unlawful act clause.